Business Competition Management in the Deepfake and Synthetic Media Era: Corporate Identity Verification as a Strategy to Mitigate Market Disinformation - Dody Waringgi; Setiasih Setiasih (Jurnal Ekonomi Balance, 2025)
This study examines business competition management in the era of deepfake and synthetic media, focusing on corporate identity verification as a strategy to mitigate market disinformation in Indonesia. The proliferation of highly realistic manipulated content poses significant risks to corporate reputation, market stability, and fair competition. Using a qualitative descriptive-analytical approach, data were collected from literature studies, policy analysis, in-depth interviews, and focus group discussions with experts in law, business, and information technology. The study identifies key threats, including instant reputation attacks using deepfake content, financial market manipulation through fabricated information, and sophisticated cybersecurity threats such as voice and video phishing. Findings highlight the urgency for companies to implement AI-based deepfake detection, strengthen multi-factor identity verification protocols, establish agile crisis response teams, and actively participate in regulatory advocacy. Additionally, raising digital literacy and promoting collaborative standards between industry and regulators are critical to safeguarding market integrity. This research contributes to both managerial practice and public policy by providing actionable strategies for businesses and regulators to counter disinformation, maintain competitive fairness, and enhance corporate resilience in a rapidly evolving digital landscape. The study underscores that proactive adaptation and swift response are no longer optional but essential for sustaining trust, stability, and transparency in Indonesia’s competitive business environment.